2020
DOI: 10.1021/acs.organomet.0c00330
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Activity and Selectivity during Alkyne Activation by Gold(I)/Platinum(0) Frustrated Lewis Pairs

Abstract: Introducing transition metals into frustrated Lewis pair systems has attracted considerable attention in recent years. Here we report a selection of three metal-only frustrated systems based on Au(I)/Pt(0) combinations and their reactivity towards alkynes. We have inspected the activation of the simplest alkyne, namely acetylene, as well as of other internal and terminal triply bonded hydrocarbons. The gold(I) fragments are stabilized by three bulky phosphines bearing terphenyl groups. We have observed that su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 81 publications
0
18
0
2
Order By: Relevance
“…Our experiments indicate that bimetallic adduct formation is not favored for zinc salts; thus, an FLP-type mechanism seems more likely. In fact, we have already demonstrated that compound 1 acts as a Lewis basic site in bimetallic FLPs by partnering it with sterically crowded Au­(I) compounds . Our prior mechanistic investigations allowed us to conclude that those Pt(0)/Au­(I) pairs mediate the cleavage of the H–H bond in dihydrogen by a genuine FLP mechanism .…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Our experiments indicate that bimetallic adduct formation is not favored for zinc salts; thus, an FLP-type mechanism seems more likely. In fact, we have already demonstrated that compound 1 acts as a Lewis basic site in bimetallic FLPs by partnering it with sterically crowded Au­(I) compounds . Our prior mechanistic investigations allowed us to conclude that those Pt(0)/Au­(I) pairs mediate the cleavage of the H–H bond in dihydrogen by a genuine FLP mechanism .…”
Section: Resultsmentioning
confidence: 78%
“…In fact, we have already demonstrated that compound 1 acts as a Lewis basic site in bimetallic FLPs by partnering it with sterically crowded Au(I) compounds. 19 Our prior mechanistic investigations allowed us to conclude that those Pt(0)/Au(I) pairs mediate the cleavage of the H–H bond in dihydrogen by a genuine FLP mechanism. 19b We wondered if the same would apply for the Pt/Zn pairs investigated herein.…”
Section: Resultsmentioning
confidence: 96%
“…Proof of this expansion is the amazing number of reports covering this area of research in continuous growing. Despite the volume of work related with this field, examples of gold-based frustrated Lewis pairs are still very limited. , Concerning homogeneous systems, special remark deserves the first and very recent gold-based FLP system [heterobimetallic species of Au­(I)/Pt(0)] developed by Campos’s group and showing sufficient FLP reactivity as a result of sterically congestion (Scheme ). This heterobimetallic FLP resulted in the activation of dihydrogen to produce a heterobimetallic dihydride.…”
Section: Sophisticated Gold Catalystsmentioning
confidence: 99%
“…An FLP is comprised of a Lewis acid and a base for which adduct formation is quenched by steric or geometric factors, leaving two reactive sites that can perform bond activation of a third species. Although the first FLPs reported were metal-free, FLPs featuring two transition-metal fragments largely increased the amount and structural diversity of Lewis acid/base combinations available, extending the catalytic usefulness of FLPs …”
Section: Bimetallic Cooperating Systemsmentioning
confidence: 99%